2018
DOI: 10.17843/rpmesp.2018.352.3250
|View full text |Cite
|
Sign up to set email alerts
|

Reordenamiento vehicular y contaminación ambiental por material particulado (2,5 y 10), dióxido de azufre y dióxido de nitrógeno en Lima Metropolitana, Perú

Abstract: Objetivos. Evaluar el cambio en los niveles ambientales de material particulado (2,5 y 10) (PM 2,5 y PM 10), dióxido de azufre (SO 2) y dióxido de nitrógeno (NO 2), posterior al reordenamiento vehicular en la avenida Abancay, entre 2013-2015 respecto a 2007-2009, comparando con otras dos avenidas sin implementación de un reordenamiento, la avenida Guillermo de La Fuente en el distrito de Comas y la avenida César Vallejo en el distrito de El Agustino. Materiales y métodos. Los datos ambientales fueron colectado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
6
0
8
Order By: Relevance
“…Most studies in Lima, Peru about contamination by PM 2.5 are restricted to describing exposure, without any association with disease [2,8,14]. On exception is the paper by , which found that for each interquartile range (IQR) increase in PM 2.5 , respiratory disease, emergency room visits in Lima increased 3% (95% CI: 1.02-1.04%) for those under 18 years [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies in Lima, Peru about contamination by PM 2.5 are restricted to describing exposure, without any association with disease [2,8,14]. On exception is the paper by , which found that for each interquartile range (IQR) increase in PM 2.5 , respiratory disease, emergency room visits in Lima increased 3% (95% CI: 1.02-1.04%) for those under 18 years [15].…”
Section: Discussionmentioning
confidence: 99%
“…Also ALRI are the leading cause of premature death in Peru, approximately 222 child deaths per year for every 100,000 live births [6]. PM 2.5 are fine particles with aerodynamic diameter of 2.5 μm or less, which are emitted from a large variety of sources including automotive vehicles, industry, power generation and engine combustion [7,8]. Some prior studies have found an association between PM 2.5 and increased health center outpatient visits for respiratory diseases [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Lima, the main sources of outdoor air pollution are automotive fleet and industrial activities [24]. A recent study showed that a change of policy regarding traffic regulation of one of Lima's main avenues, significantly decreased PM 2.5 values [25], meaning that similar changes may have an impact improving air quality.…”
Section: Resultsmentioning
confidence: 99%
“…En Latinoamérica, Lima Metropolitana es una de las áreas metropolitanas más contaminadas, con el 80 % de polución, que es consecuencia de su parque automotor obsoleto, conforme lo ha indicado la Organización Mundial de la Salud, lo que va aunado a la pésima calidad de los combustibles (Vilma Tapia, 2018).…”
Section: Introductionunclassified